The Need for the Enactment of Prize Law Legislation in Indonesia - Yoga, Pornomo Rovan Astri (Indonesian Journal of International Law, 2025)
Indonesia is a peace-loving nation. However, maintaining independence is more precious than maintaining peace. Therefore, Indonesia will always be ready to maintain its independence at any cost, including war. Indonesia claims itself as a maritime nation. All of those facts disregard the point that Indonesia lacks legislation regarding the law of naval warfare. This is particularly true in the case of the prize law. There are no single laws, statutes, or even procedures that govern the prize law in times of armed conflict at sea. The practice of the prize law has also been lacking since Indonesia’s independence in 1945. Even though the prize law is an old body of law, its applicability is still likely in the future’s armed conflict at sea. For this body of law to be applicable, many variables need to be discussed, especially regarding the relations between Indonesia’s domestic law and international law. The need for the accession of international treaties related to the prize law is also an important subject matter. This article found that the non-existence of the prize law means that there is a big gap in the law that needs to be filled.